Identification and Characterization of Buffalo 7SK and U6 pol III Promoters and Application for Expression of Short Hairpin RNAs - Zhang, Xiaoxi (Molecular Diversity Preservation International (MDPI), 2014)
RNA polymerase III (pol III) type 3 promoters, such as 7SK and U6, are routinely used to induce short hairpin RNAs (shRNAs) to knockdown gene expression by RNA interference (RNAi). To extend the application of RNAi to studies of buffalo, an shRNAs expressing system using the buffalo pol III promoters was developed. Buffalo 7SK promoter (bu7SK) and U6 promoter (buU6) sequences upstream of the full-length 7SK and U6 small nuclear RNA sequence in the buffalo genome were identified and characterized, respectively. To determine the functionality of these promoters in constructs driving shRNA expression, anti-EGFP shRNAs (shEGFP) cassettes under the direction of bu7SK and buU6 were constructed. We further compared the EGFP knockdown efficiency of constructs using bu7SK and buU6 with that of promoters of human and bovine origins in BFF cells and mouse PT67 cells by flow cytometry and quantitative real-time PCR assays. We found that the bu7SK and buU6 promoters induced the greatest level of suppression in homologous and heterologous cells relative to promoters derived from other species. Taken together, functional bu7SK and buU6 promoters were identified and characterized, thus laying the groundwork for future development of RNAi therapeutics and gene modification in buffalo species.